2002
DOI: 10.1079/nrr200131
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional influences on cognitive function: mechanisms of susceptibility

Abstract: The impact of nutritional variation, within populations not overtly malnourished, on cognitive function and arousal is considered. The emphasis is on susceptibility to acute effects of meals and glucose loads, and chronic effects of dieting, on mental performance, and effects of cholesterol and vitamin levels on cognitive impairment. New developments in understanding dietary influences on neurohormonal systems, and their implications for cognition and affect, allow reinterpretation of both earlier and recent f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(41 citation statements)
references
References 248 publications
3
37
0
Order By: Relevance
“…In contrast, participants of AP session reported contrary results. Evidence indicates that macronutrient composition may influence mood by affecting the synthesis of monoamine neurotransmitters [47]. It has been suggested that carbohydrate-rich meals lead to increased fatigue and decreased alertness, whereas meals rich in protein increase alertness and decrease drowsiness [48,28].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, participants of AP session reported contrary results. Evidence indicates that macronutrient composition may influence mood by affecting the synthesis of monoamine neurotransmitters [47]. It has been suggested that carbohydrate-rich meals lead to increased fatigue and decreased alertness, whereas meals rich in protein increase alertness and decrease drowsiness [48,28].…”
Section: Discussionmentioning
confidence: 99%
“…These data can rely on five-way theory (Macht, 2008), which proposes that negative emotions can increase food intake (Gibson and Green, 2002;Macht & Mueller, 2007), i.e. this theory relates lack of skills to manage emo-anales de psicología, 2018, vol.…”
Section: Discussionmentioning
confidence: 99%
“…According to the author, emotion intensity can vary an individual's diet: high intensity emotions would cause a reduction in food consumption, and moderate emotions would increase it. Likewise, several authors propose that the increase in the desire to eat in a previous restriction situation may be due to deterioration of cognitive control (Boon, Stroebe, Schut & Jansen, 1998;Lattimore & Maxwell, 2004;Wallis & Hetherington, 2004) or negative emotions themselves (Gibson & Green, 2002;Macht & Mueller, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Sixth, desirable foods contain nutrients that are likely to have a direct physiological and perhaps also indirect psychological impact (Drewnowski, 1997;Leigh Gibson, & Green, 2002;Van Oudenhove et al, 2011). Whilst this nutrient-based physiological mechanism was clearly not contributing to the impact of gifting it may have played a role during the eating condition.…”
Section: Study)mentioning
confidence: 99%